Proses Pengambilan Keputusan Nasabah Bank Syariah Dalam Memilih Produk Pembiayaan Kepemilikian Rumah (Studi Kasus Nasabah Bank Muammalat KCI Darmo Surabaya) - Bima Kurnia Putra; Fatin Fadhilah Hasib (Universitas Airlangga, 2014)
The purpose of this research is to find out the decision making process of the customer of Muamalat Bank in choosing mortgage product. The process comprises problem recognition, information search, evaluation of alternatives, product choice, and the outcomes.A qualitative approach is applied in this research with the descriptive case study method. The collection of data uses purposive sampling to determine the key informant and uses snowballing sampling to determine the informants. The key informant in this research is an employee of Muamalat Bank. Meanwhile the infomants consist of four customers of Muamalat Bank. Two of them take murabahah contract and the rest takes musyarakah mutanaqisah contract. The collection of data is conducted through several steps including comprehensive exploration, focus exploration, and confirmation step. The data analysis in this research uses domain, taxonomic and componential analysis.The result of this research shows that both the murabahah and musyarakah mutanaqisah customers had already passed through five steps in decision making process comprises problem recognition, information search, evaluation of alternatives, product choice, and outcomes. The difference between two of them is revealed in the problem recognition and the product choice. The customer choose the mortgage contract based on some features. REFERENCESAntonio, Muhammad Syafi’I. 2001. Bank Syariah Dari Teori Ke Praktik. Jakarta: Gema Insani.Hasib, Fatin Fadhilah, Suprayogi Noven, Hapsari Meri Indri. 2012. Hibah Riset Fakultas Ekonomi dan Bisnis Universitas Airlangga:Implikasi Manajemen Risiko Terhadap Pemilihan Akad Pembiayaan Kepemilikan Rumada Pada Perbankan Syariah Surabaya.Hausel, John R, Urban, Glen L, and Weinberg, Bruce D. 1993. Journal of Consumer Research: How Consumers Allocate Their Time When Searching for Information.Kotler Philip and Amstrong, Gary. 2001. Principles of Marketing (Ninth Edition). New Jersey:Prentice Hall,Inc.Kotler, Philip. 2006. Manajemen Pemasaran. Edisi Kesebelas. Jilid 1. Terjemahan Oleh Benyamin Moan. 2006. Jakarta:indkes.Solomon, M. R. 2007. Consumer Behavior: Buying, Having, and Being. New Jersey, Upper Saddle River: Pearson Educatio n, Inc.Yogaswara, Rhesa. 2010. Skema Pembiayaan Perumahan Syariah. Seminar Internasional IBFI Trisakti:Potensi Lembaga Keuangan Syariah Mikro Dalam Skema Pembiayaan Perumahan Secara Syariah.Yin, Robert. 2002. Studi Kasus Desain dan Metode. Jakarta:PT Raja Grafindo Persada.